Potential of Bioactive Compounds of Allium sativum L. var. solo garlic Extract in Inhibiting InhA Protein in Mycobacterium tuberculosis - Rohmawati, Uun; Amalia, Atikah (Jurnal Biologi Tropis, 2025)
Tuberculosis (TB) is caused by the bacteria Mycobacterium tuberculosis. In general, TB is treated with compounds that inhibit the work of one of the enzymes in the bacteria Mycobacterium tuberculosis, namely the InhA enzyme. One of the herbal plants that has the potential to inhibit the InhA protein in the bacteria Mycobacterium tuberculosis is. Allium sativum L. var. solo garlic. This research aims to determine the bioactive compounds in Allium sativum L. var. solo garlic in inhibiting the InhA protein in Mycobacterium tuberculosis which can be used as an alternative drug in the treatment of TB through an in silico approach. The method used in this study was qualitative phytochemical screening and GCMS test on Allium sativum L. var. solo garlic extract, the bioactive compounds found were tested in silico through a molecular docking approach. The research results obtained that Allium sativum L. var. solo garlic contains alkaloids, flavonoids, tannins and steroids. Based on the results of the GCMS test, the bioactive compounds that have an area of ​​more than 5% are Heptadecene-(8)-Carbonic Acid-(1), 3-Deoxy-D-Mannonic Acid, 5-Hydroxymethylfurfural, Melezitose and Oleic acid. The results of molecular docking showed that the compound 3-Deoxy-D-mannonic acid had a binding affinity of -4.9, 5-Hydroxymethylfurfural -4.8, Oleic Acid -6.4, Nicotinamide-Adenine-Dinucleotide (Control) had a binding affinity of -11.4. Low binding affinity indicates that the compound can bind to the protein with little energy. The Gyps energy theory states that the smaller the energy produced from a bond between the ligand and its receptor, the more stable the bond is. The lowest binding energy to the InhA protein is in the control compound Nicotinamide-Adenine-Dinucleotide, Oleic Acid, 3-Deoxy-D-mannonic acid, 5-Hydroxymethylfurfural.